The Productive Performance of Intercrops under Fodder Tree Species based Agroforestry Systems in Northern Transitional Zone of Dharwad Region of Karnataka - Shahapurmath, Girish; Inamati, Shivakumar (Indian Journal of Agroforestry, 2025)
The present field investigation was carried out in existing fodder plantation for two years during kharif and rabi seasons of 2018-19 and 2019-20 to study the effect of different fodder tree species on intercrops (Soybean and Safflower) grown under fodder tree based agroforestry system at University of Agricultural Sciences, Dharwad, Karnataka. The experiment was laid out in Randomized Block Design (RBD) with three replications in an established plantation. Fodder trees were planted at a spacing of 5 × 3 m and the plot size was 15 × 12 m with 12 trees per treatment with two intercrops soybean (kharif season) and safflower (rabi season) in the interspaces. During kharif season, the yield attributes of soybean (number of pods, seed weight, hundred seed weight, seed yield and haulm yield) were noticed highest values in sole soybean (T8). Whereas, Albizia lebbeck + Soybean (T2) recorded maximum values among agroforestry systems during both the periods of investigation. The highest number of root nodules and weight of root nodules were recorded in soybean as sole crop (T8) and Albizia lebbeck + Soybean (T2) agroforestry system. During rabi season, the yield attributes of safflower (number of capitula, seed yield and haulm yield) were recorded maximum values in sole safflower (T8). Among agroforestry systems, Moringa oleifera + Safflower (T6) noticed maximum values during both the periods of investigation. The fodder tree based agroforestry systems reported a significant influence on soil moisture (%) with soybean and safflower intercrops in different growth stages (20, 40, 60 DAS and at harvest) during study periods which indicated water stored in the soil helps in performance of field crops. Soil moisture (%) under soybean crop showed decreasing trend from 20 DAS to harvesting stage.